Impact of Dibutyl Phthalate (Dbp) on Sgot and Sgpt in Goldfish (Carassius Auratus) with Therapeutic Efficacy Withania Somnifera (International Journal of Environmental Sciences, 2024)
The increasing use of plasticizers such as dibutyl phthalate (DBP) in industrial and domestic products has raised significant concerns about their environmental toxicity, particularly in aquatic ecosystems. DBP, a widely used phthalate ester, is known for its endocrine-disrupting and hepatotoxic properties. The present study investigates the impact of DBP exposure on hepatic function in goldfish (Carassius auratus), as measured by serum levels of liver enzymes viz. serum glutamic oxaloacetic transaminase (SGOT) and serum glutamic pyruvic transaminase (SGPT). Additionally, the study evaluates the therapeutic efficacy of Withania somnifera, commonly known as ashwagandha, a medicinal plant with known antioxidant and hepatoprotective properties, in mitigating DBP-induced hepatic damage. Goldfish were divided into three groups- control, DBP-exposed, DBP + Withania somnifera treated. Fish in the DBP-exposed group were subjected to a sub-lethal concentration of DBP followed by treatment with Withania somnifera extract in the therapeutic group. SGOT and SGPT levels were measured using standard biochemical assays through standard kit. Results demonstrated a significant increase in SGOT and SGPT levels in DBP-exposed fish, indicating hepatocellular injury. However, fish treated with Withania somnifera following DBP exposure showed a marked reduction in these enzyme levels, approaching normalcy compared to control. This suggests the hepatoprotective role of Withania somnifera, likely due to its antioxidative and anti-inflammatory bioactive compounds such as withanolides. In conclusion, DBP exerts a detrimental effect on liver function in Carassius auratus, as evidenced by elevated SGOT and SGPT. Withania somnifera demonstrates promising therapeutic potential in ameliorating DBP-induced hepatic toxicity, highlighting its relevance as a natural remedy in aquatic toxicology and fish health management. Further studies are recommended to elucidate the molecular pathways involved in its protective mechanism.